Design Of Project Story Book Development Based On Local Wisdom Of Kudus District - Rofah, Aisyah; Santoso, Santoso; Suryani, Fitri Budi (Journal Prakarsa Paedagogia, 2022)
Kudus regency is one of the districts in Central Java, Indonesia. Before Islam entered, Kudus district was named Tajug village, which means a fertile area stranded between the Tanggulangin river and the Juwana river to the east. The design of project story book development is a form of solution to existing problems, namely attracting early childhood interest and learning about local wisdom in the Kudus district. This study discuss the design of the project story book that was made. The research method used in this research is descriptive qualitative. The data obtained are results of literature studies in the form of book, journals, interview with competent people and observastions. The result of this research is the creation of a project story book aimed at early childhood in Kudus district.